Durability and Long-Term Clinical Outcomes of Fecal Microbiota Transplant (FMT) Treatment in Patients with Recurrent C. difficile Infection. (4th October 2017) - Mamo, Yafet; Woodworth, Michael; Sitchenko, Kaitlin; Dhere, Tanvi; Kraft, Colleen
Abstract: Background: Fecal microbiota transplant (FMT) has been shown to be safe and effective for treatment of recurrent C. difficile infection (RCDI). The aim of this study is to determine factors impacting the durability of FMT and assess patient long-term clinical outcomes and satisfaction with the procedure. Methods: Eligible patients who had received FMT for RCDI at Emory Hospital between July 1, 2012 and December 31, 2016 were contacted via telephone for a follow up survey. Of 232 patients who received FMT, 27 were deceased and 15 were unable to be reached with listed phone number. Of the remaining 190 eligible patients, 137 patients completed the survey. Results: The median time-period between FMT and follow up was 22 months. Median number of failed antibiotic courses for RCDI before FMT was 4. Overall, 82% (113/137) of patients experienced resolution of RCDI post-FMT (non-RCDI group) while 18% (24/137) of patients had recurrence of CDI post-FMT (RCDI group). In the RCDI and non-RCDI groups, antibiotic use post-FMT for non- C. difficile-related infections was 75% and 38% ( P = 0.0004), respectively. PPI use post-FMT was 38% and 31% ( P = 0.28), and probiotic use post-FMT was 63% and 41% ( P = 0.026) in the RCDI and non-RCDI groups, respectively. There were 18 hospitalizations in the RCDI group and 9 were related to C. difficile complications; of the 36 hospitalizations in the non-RCDI group, only 1 was related to chronic complication of a previous C. difficile infection. Overall, 11% of patients reported improvement or resolution of medical conditions not related to CDI post-FMT while 33% reported diagnosis of a new medical condition or development of new symptoms; none of the new medical conditions or symptoms were attributable to the procedure. In all, 95% of patients indicated willingness to undergo FMT in the future if they experience another bout of C. difficile infection. Conclusion: The findings show that FMT is a highly effective treatment option for RCDI with a cure rate, defined as resolution of RCDI post-FMT or recurrence attributable to antibiotic use post-FMT, of 96% (131/137) in the study group. Furthermore, clinical outcomes and patient satisfaction post-FMT indicate the safety of the procedure. Disclosures: All authors: No reported disclosures.